2013
DOI: 10.1089/neu.2012.2431
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mild Traumatic Brain Injury with an Erythropoietin-Mimetic Peptide

Abstract: Mild traumatic brain injury (mTBI) results in an estimated 75-90% of the 1.7 million TBI-related emergency room visits each year. Post-concussion symptoms, which can include impaired memory problems, may persist for prolonged periods of time in a fraction of these cases. The purpose of this study was to determine if an erythropoietin-mimetic peptide, pyroglutamate helix B surface peptide (pHBSP), would improve neurological outcomes following mTBI. Sixty-four rats were randomly assigned to pHBSP or control (ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Erythropoietin derivatives that can promote nonhematopoietic tissue protective effects, especially neuroprotection and cardioprotection, without stimulating erythropoiesis, have been proposed to bind alternate EPO receptors such as the EPOR/βc receptor heterodimer. These include asialoerythropoietin, carbamylated EPO, ARA 290 [cibinetide; helix B surface peptide (11 amino acid peptide derived from the EPO sequence)], and recombinant EV-3 (an EPO derived a spliced variant with exon 3 deleted) (Erbayraktar et al, 2003;Brines et al, 2004Brines et al, , 2008Fiordaliso et al, 2005;Robertson et al, 2013;Bonnas et al, 2017). Clinical studies explored the safety and use of EPO and carbamylated EPO to increase frataxin levels for treatment of Friedreich's Ataxia (Boesch et al, 2014;Egger et al, 2014;Santner et al, 2014).…”
Section: Alternate Epo Receptors and Epo Derivativesmentioning
confidence: 99%
“…Erythropoietin derivatives that can promote nonhematopoietic tissue protective effects, especially neuroprotection and cardioprotection, without stimulating erythropoiesis, have been proposed to bind alternate EPO receptors such as the EPOR/βc receptor heterodimer. These include asialoerythropoietin, carbamylated EPO, ARA 290 [cibinetide; helix B surface peptide (11 amino acid peptide derived from the EPO sequence)], and recombinant EV-3 (an EPO derived a spliced variant with exon 3 deleted) (Erbayraktar et al, 2003;Brines et al, 2004Brines et al, , 2008Fiordaliso et al, 2005;Robertson et al, 2013;Bonnas et al, 2017). Clinical studies explored the safety and use of EPO and carbamylated EPO to increase frataxin levels for treatment of Friedreich's Ataxia (Boesch et al, 2014;Egger et al, 2014;Santner et al, 2014).…”
Section: Alternate Epo Receptors and Epo Derivativesmentioning
confidence: 99%
“…One promising candidate is ARA 290, which is an 11-amino acid peptide modeled from the three dimensional structure of helix B of the EPO molecule that interacts with the IRR (8). ARA 290 has been evaluated extensively in a wide spectrum of preclinical models, including diet-induced insulin resistance (10), diabetic retinopathy (11), diabetic autonomic neuropathy (12), myocardial infarction (13), chronic heart failure (14), burns (15), traumatic brain injury (16,17) and shock-induced multi-organ failure (18), among others. The results of these studies show that ARA 290 prevents tissue injury, reduces inflammation and activates healing.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic administration of recombinant human erythropoietin (rhEPO) was found to induce a significant reduction of inflammation and cell apoptosis, together with improved functional recovery after focal TBI in mice (17). Improved cognitive function was found in rats treated with erythropoietin-mimetic peptide after mild TBI (18). Using the impact-acceleration model to induce diffuse TBI in rats, we found that rhEPO and carbamylated erythropoietin, a modified erythropoietin lacking erythropoietic activity, blocked the development of posttraumatic cellular edema as early as 1 hour after the insult (19,20).…”
mentioning
confidence: 99%